The perceived value of a multi-sensory design approach on the experience of consumers relating to the coffee shop phenomenon in South Africa. - Brown, Tyla (The IIE, 2022)
In order to give customers a better experience, this study aims to investigate and narrow down the effects of using a multi-sensory design approach in the interior of Starbucks coffee shops. This can then assist coffee shops in considering how to design a space to include more multi-sensory environments that affect the experience of the consumers. The results of this study have the potential to increase our understanding of the impact multi-sensory design has on coffee shop interiors. By investigating the effects of using a multi-sensorial design approach when it comes to designing the interior spaces of a coffee shop, the interpretivism paradigm is used in this study to gain a thorough understanding of the experiences of the customers. The researcher plans to use a qualitative design approach because it is well known for studying human behaviour in daily life and involves ongoing research with consumers in order to understand how they interpret the environments of coffee shops. The researcher plans to use five coffee shop consumers as participants for this study, including men and women of all ages between 19 and 25. The researcher will employ a non-probability sampling technique because it avoids using a random sample of population components. Given that the researcher wants to focus on a younger customer demographic, purposive sampling will be used. In-depth interviews or questionnaires with open-ended questions will be used to collect data for this study. A thematic analysis, also known as theming, will be used to interpret the collected data.
Keywords: Consumer behaviour; Interior design; Retail; User centered design; Biophilia